Compound option valuation for a coal bed methane development project. Issue 5 (2nd September 2016) - Yoon, Young; Kim, Jinsoo
Abstract: There are many uncertainties in coal bed methane (CBM) projects: gas price fluctuations according to oil prices, changes of operational and capital costs, development and production lifetimes and production volume from underground conditions. It is well known that ordinary discounted cash flow method cannot consider these uncertainties. The real option method can evaluate them properly by reflecting managerial flexibility in an uncertain environment. The option valuation for unconventional oil and gas assets is thus important since a management design is the key for a successful development. In this context, a compound real option approach is applied to evaluate a CBM development project. We evaluated defer and abandon options considering the different uncertainties in an exploration stage and the other stage. The analysis results reveal expanded value of the CBM project by stage and option. We can thus provide rich information for decision-makers of energy projects through this approach.